2012
DOI: 10.1161/hypertensionaha.111.189571
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper Transport Protein Antioxidant 1 in Angiotensin II–Induced Hypertension

Abstract: Extracellular superoxide dismutase (SOD3) is a secretory copper enzyme involved in protecting angiotensin II (Ang II)-induced hypertension. We previously found that Ang II upregulates SOD3 expression and activity as a counter-regulatory mechanism; however, underlying mechanisms are unclear. Antioxidant-1 (Atox1) is shown to act as a copper-dependent transcription factor as well as copper chaperone for SOD3 in vitro, but its role in Ang II-induced hypertension in vivo is unknown. Here we show that Ang II infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 37 publications
2
58
0
1
Order By: Relevance
“…These pioneering studies were subsequently replicated in a mammalian system, where genetic inactivation of a mouse Atx1 ortholog (Atox1) was found to greatly impair copper delivery from placenta to fetus resulting in copper deficiency and high mortality of newborn pups (29). More recent studies using Atox1 -/ -mice with a different genetic background found less copper deficiency and mortality compared to the earlier report (72). However, this latter study revealed a significant inhibitory effect of Atox1 inactivation on copper delivery (via Cu-ATPase ATP7A) to SOD3, an important antioxidant molecule at the cell surface.…”
Section: Discovery Of Dual Function Of Atox1mentioning
confidence: 90%
See 2 more Smart Citations
“…These pioneering studies were subsequently replicated in a mammalian system, where genetic inactivation of a mouse Atx1 ortholog (Atox1) was found to greatly impair copper delivery from placenta to fetus resulting in copper deficiency and high mortality of newborn pups (29). More recent studies using Atox1 -/ -mice with a different genetic background found less copper deficiency and mortality compared to the earlier report (72). However, this latter study revealed a significant inhibitory effect of Atox1 inactivation on copper delivery (via Cu-ATPase ATP7A) to SOD3, an important antioxidant molecule at the cell surface.…”
Section: Discovery Of Dual Function Of Atox1mentioning
confidence: 90%
“…However, this latter study revealed a significant inhibitory effect of Atox1 inactivation on copper delivery (via Cu-ATPase ATP7A) to SOD3, an important antioxidant molecule at the cell surface. In addition, downregulation of SOD3 mRNA and protein in response to Atox1 inactivation was observed, making connection between copper metabolism and anti-oxidant defense even more intertwined (72 These findings opened an avenue for intensive investigations of biochemical properties of Atox1 and the mechanism of Atox1-mediated copper delivery to the secretory pathway. Over the years, great progress has been made in these areas Copper enters the cell through the high-affinity copper transporter Ctr1 and binds to cytosolic copper chaperones (Atox1 and CCS) and/or small thiol molecules such as glutathione for further intracellular distribution (''Labile'' Cu pool).…”
Section: Discovery Of Dual Function Of Atox1mentioning
confidence: 95%
See 1 more Smart Citation
“…The physical association between ATP7A and SOD3 in angiotensin II-treated mutant mice attests to the attempt to rescue the increase of vascular superoxide through an enhanced loading of the antioxidant cuproenzyme with copper [141]. Ozumi et al [142] pointed out the role of the cytosolic copper transport protein ATOX1, from which ATP7A pumps obtain copper ions, in the vascular response to angiotensin II. The importance of ATOX1 in such a context is emphasized by the restricted intracellular copper content (10 -18 M ) [76].…”
Section: Role Of Copper Transport Systems During Angiogenesismentioning
confidence: 99%
“…The importance of ATOX1 in such a context is emphasized by the restricted intracellular copper content (10 -18 M ) [76]. An enhanced copper egress from endothelia has been detected in response to angiotensin II, associated with active SOD3 biosynthesis and release [142]. Interestingly, a recent study on vascular complications in diabetes mellitus induced in mice evidenced a reduced expression of ATP7A in blood vessels, associated with an impairment of SOD3 activity [143].…”
Section: Role Of Copper Transport Systems During Angiogenesismentioning
confidence: 99%